Protective and Therapeutic Efficacy of Hesperidin versus Cisplatin against Ehrlich Ascites Carcinoma-Induced Renal Damage in Mice - Nahed Saleh; Tamer Allam; Reda M. S. Korany; Abdelfattah M. Abdelfattah; Ahmed M. Omran; Mabrouk Attia Abd Eldaim; Aziza M. Hassan; Nermeen Borai El-Borai (MDPI AG, 2022)
This study evaluates the antitumor efficacy of hesperidin (Hesp) versus cisplatin (Cis) in Ehrlich ascites carcinoma (EAC)-bearing mice, as well as its protective effect against Cis-triggered nephrotoxicity. Seventy female mice were allocated into control, Hesp, EAC, Hesp-protected, Hesp-treated, Cis-treated, and Cis+Hesp-treated groups. The inoculation of mice with EAC cells significantly reduced the mean survival time, while significantly increased the body weight, abdominal circumference, ascitic fluid volume, viable tumor cell count, and serum carcinoembryonic antigen, urea and creatinine levels, besides various hematological changes. Additionally, kidney tissue of EAC-bearing mice showed a significant increase in the malondialdehyde level, significant decreases in the reduced glutathione content and catalase activity, marked pathological alterations, and a strong Ki-67 expression with a weak caspase-3 expression in neoplastic cells infiltrating the renal capsule. Conversely, the administration of Hesp and/or Cis to the EAC-bearing mice induced, to various degrees, antitumor responses and alleviated the cytotoxic effects of EAC. In addition to the potent antitumor effect of the concomitant administration of Hesp and Cis, Hesp minimized the renal adverse side effects of Cis. In conclusion, Hesp may open new avenues for safe and effective cancer therapy and could be valuable for enhancing the antitumor potency and minimizing the renal adverse side effects of chemotherapeutic drugs.